2019
DOI: 10.3390/ijerph16101694
|View full text |Cite
|
Sign up to set email alerts
|

From Complex Interventions to Complex Systems: Using Social Network Analysis to Understand School Engagement with Health and Wellbeing

Abstract: Challenges in changing school system functioning to orient them towards health are commonly underestimated. Understanding the social interactions of school staff from a complex systems perspective may provide valuable insight into how system dynamics may impede or facilitate the promotion of health and wellbeing. Ego social network analysis was employed with wellbeing leads within four diverse case study schools to identify variability in embeddedness of health and wellbeing roles. This variation, as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Second is the importance of supporting staff who are confident in delivering health promotion and believe in its value. These facilitators are consistent with studies of the implementation of school health interventions [13,31,67], suggesting factors are crucial to both phases.…”
Section: Summary Of Key Findingssupporting
confidence: 83%
“…Second is the importance of supporting staff who are confident in delivering health promotion and believe in its value. These facilitators are consistent with studies of the implementation of school health interventions [13,31,67], suggesting factors are crucial to both phases.…”
Section: Summary Of Key Findingssupporting
confidence: 83%
“…Specific actions that can help teachers to advocate for wellness training include: Have district leadership use formal and informal communication processes to engage teachers in the discussion and selection of SWP goals. Identify free and low‐cost professional development opportunities for nutrition education and physical activity that can be provided to school staff via virtual teaching methods. At the school/district level, we found that general/academic leaders are often responsible for monitoring the implementation of the SWP. Although inclusion of general/academic leaders is important for the success of school health programming, distribution of leaders among multiple stakeholders, including nutrition and physical education staff, can help orient districts toward wellness 33 . Additionally, in Texas, school health advisory committees play an important role in setting/evaluating district‐level health priorities, which suggest that they could play a larger role in monitoring SWPs.…”
Section: Implications For School Health and Equitymentioning
confidence: 99%
“…Most studies found a negative association between student–teacher relationships (STR) and the risk factor of dropping out ( Lee and Burkam, 2003 ; Murray and Malmgren, 2005 ; Barile et al, 2011 ; Bergeron et al, 2011 ; Wang et al, 2013 ; Frostad et al, 2014 ; Littlecott et al, 2019 ; Song, 2021 ; Zheng, 2021 ). This means that in schools where there is a positive STR, there are low dropout rates.…”
Section: Summary Of Resultsmentioning
confidence: 99%